2000
DOI: 10.1046/j.1365-3024.2000.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential ability of specific regions of Plasmodium falciparum sexual‐stage antigen, Pfs230, to induce malaria transmission‐blocking immunity

Abstract: Antibodies raised against an Escherichia coli-produced recombinant protein encoding a 76-kDa section (region C) of malaria transmission-blocking vaccine candidate, Pfs230, have previously been shown to significantly reduce the ability of Plasmodium falciparum parasites to infect mosquitoes (71.2-89.8%). To further define the region of the Pfs230 required for transmission-blocking activity, four recombinant proteins each encoding a section of region C (Pfs230 amino acids 443-1132) were produced using the same E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 17 publications
2
37
1
Order By: Relevance
“…In this study, we expressed, purified, and characterized 230CMB (aa 444 to 730). The 230CMB antigen described here is similar to r230/MBP.C5 (aa 443 to 791) produced by Bustamante et al (2), which comprises the region of Pfs230 positioned just after the N-terminal cleaved domain until midway through the first cysteine motif domain and contains four cysteine residues. However, unlike the MBP fusion, 230CMB is a stand-alone soluble antigen which is recognized in both Western blot assays and ELISA by two different anti-Pfs230 MAbs possessing TB activity.…”
Section: Discussionmentioning
confidence: 88%
“…In this study, we expressed, purified, and characterized 230CMB (aa 444 to 730). The 230CMB antigen described here is similar to r230/MBP.C5 (aa 443 to 791) produced by Bustamante et al (2), which comprises the region of Pfs230 positioned just after the N-terminal cleaved domain until midway through the first cysteine motif domain and contains four cysteine residues. However, unlike the MBP fusion, 230CMB is a stand-alone soluble antigen which is recognized in both Western blot assays and ELISA by two different anti-Pfs230 MAbs possessing TB activity.…”
Section: Discussionmentioning
confidence: 88%
“…In previous studies (4,43), transmission-blocking antibodies against Pfs230C were effective only at a higher concentration (i.e., a 1:2 dilution).…”
Section: Discussionmentioning
confidence: 90%
“…An oligo microarray study on Chr 2 of Plasmodium showed that 69% of all polymorphisms detected were in membrane-associated genes in telomeric and subtelomeric regions and that polymorphism is rather rare elsewhere in the genome (Volkman et al 2002). The highly polymorphic genes included Var genes involved in antigenic variation (Bull et al 1998;Newbold 1999), vaccine targets such as pfs230 (Bustamante et al 2000;Williamson 2003), and merozoite antigens (M. K. Hughes and A. L. Hughes 1995) for which there is independent evidence of positive selection from sequence comparisons. Furthermore, many other polymorphisms were found in unknown genes that may also be surface expressed and exposed to immune selection (Volkman et al 2002).…”
Section: Genetic Structure At Selected and Neutral Loci 2369mentioning
confidence: 99%